2020
DOI: 10.1097/md.0000000000020127
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis in elective spinal surgery

Abstract: Background: Venous thromboembolism (VTE) is a serious, sometimes life-threatening complication that can occur following spine surgery. The incidence of VTE, and the optimal type and timing of thromboprophylaxis for this complication in elective spine surgery is a matter of debate. Objective: To perform a systematic review with the aim of clarifying the efficacy and adverse effects of mechanical and chemical prophylaxis for preventing thromboembolic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Venous thromboembolism is a common postoperative complication that can raise the risks of morbidity and mortality [7 , 11] . Because of this, prevention of VTE has been heavily studied among other orthopedic and trauma surgery populations [12] . For instance, there is robust evidence to suggest that prophylactic anticoagulation significantly reduces the occurrence of VTE after hip and knee arthroplasty [41] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Venous thromboembolism is a common postoperative complication that can raise the risks of morbidity and mortality [7 , 11] . Because of this, prevention of VTE has been heavily studied among other orthopedic and trauma surgery populations [12] . For instance, there is robust evidence to suggest that prophylactic anticoagulation significantly reduces the occurrence of VTE after hip and knee arthroplasty [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Although SEHs are infrequent, they can cause devastating neurologic injury [9] , leading many surgeons to avoid the use of anticoagulants during elective spinal surgery [10] . When VTE chemoprophylaxis is used, the optimal timing of administration to maximize the benefits of anticoagulation whereas minimizing bleeding risks remains unclear [11 , 12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced pain and opioid consumption, together with a comprehensive ERAS approach and reduced LOS, should theoretically hasten the mobilisation of the patients and reduce their need for thromboprophylaxis or risk for venous thromboembolism, which is a crucial issue in neurosurgery [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 82 , 83 It is difficult to decide the optimal strategy for VTE prevention because trauma patients may have real or perceived contraindications to prophylaxis, which affects the timing of preventive measures. A meta-analysis 84 showed that the optimal plan for the prevention of traumatic VTE has not been reached, due to many factors such as the poor study quality, study design, population characteristics, outcome definition, etc. Chemical anticoagulation has clear therapeutic effects, but there is an unavoidable risk of bleeding.…”
Section: Treatment and Prevention Of Trauma Vtementioning
confidence: 99%